The impact of social media marketing on consumer behaviour in the food and beverage (F&B) industry in the Klang valley during covid-19 - Tee, Ju Yi (2022)
The goal of this article is to examine the significance between social media marketing and consumer behaviour during the COVID-19 pandemic in Malaysia. The research was conducted in the Malaysian food and beverage industry and focused on how social media influences consumer behaviour. Residents of the Klang Valley in Malaysia were the target respondents for this study. There are 258 valid respondents took part in this study by filling out an online questionnaire sent to them. This research has four independent variables: a) social media advertising; b) Electronic Word-of Mouth (E-WOM); c) online order and delivery systems; d) cashless payments and one dependent variables, consumer behaviour. Based on the Stimulus-Response (SR) paradigm and the Theory of Planned Behaviour (TPB), the link between them has been examined. In addition, descriptive analysis, inferential analysis, correlation analysis, and multiple regression analysis are employed to determine the importance of both variables. Due to the accessibility of food delivery applications, the results imply that E-WOM has the highest significant with consumer behaviour, whereas online order and delivery systems have the least relationship. In the end, a discussion of the studies' limitations and recommendations have shown.